Photon-induced cell migration and integrin expression promoted by DNA integration of HPV16 genome Die genomische Integration von HPV16-DNS begünstigt eine photonenstimulierte Integrinexpression und Zellmigration - Rieken, Stefan; Simon, Florian; Habermehl, Daniel; Dittmar, Jan Oliver; Combs, Stephanie E.; Weber, Klaus; Debus, Juergen; Lindel, Katja (Strahlentherapie und Onkologie, 2014)
Background: Persistent human papilloma virus 16 (HPV16) infections are a major cause of cervical cancer. The integration of the viral DNA into the host genome causes E2 gene disruption which prevents apoptosis and increases host cell motility. In cervical cancer patients, survival is limited by local infiltration and systemic dissemination. Surgical control rates are poor in cases of parametrial infiltration. In these patients, radiotherapy (RT) is administered to enhance local control. However, photon irradiation itself has been reported to increase cell motility. In cases of E2-disrupted cervical cancers, this phenomon would impose an additional risk of enhanced tumor cell motility. Here, we analyze mechanisms underlying photon-increased migration in keratinocytes with differential E2 gene status.
CRIS-Team Scopus Importer:2023-03-08
Keywords: E2 gene; Human papillomavirus; Migration; Radiosensitizer; Uterine cervical neoplasms